Nevus lipomatosus cutaneous superficialis: Clinicopathological spectrum of six cases from an Indian archipelago - Seetu Palo; Pradeep Balasubramanian; Ashwinkumar K Barsagade (Wolters Kluwer Medknow Publications, 2022)
Nevus lipomatosus cutaneous superficialis (NLCS) is a rare cutaneous hamartomatous lesion, histopathologically characterized by the presence of ectopic dermal adipocytes. Herein, reported is the clinicopathological aspect of six cases of NLCS, consisting of three males and three females, with age at presentation ranging from 18 to 47 years and duration of lesion ranging from 2 to 18 years. Out of the six cases, five were of solitary NLCS, who presented with nodules or polypoidal masses of variable sizes and duration. The lone case of classical NLCS presented with multiple skin-coloured cerebriform nodules over the right lower back in zosteriform distribution. The commonest location was lower back and thigh. Histopathological examination revealed lobules of mature adipocytes in the papillary and/or reticular dermis in all cases, thereby establishing the diagnosis of NLCS. Additional microscopic features encountered were surface ulceration, focal myxoid degeneration, mild perivascular lymphocytic infiltrate and attenuation of adnexal structures.